2018
DOI: 10.1186/s12863-017-0594-3
|View full text |Cite
|
Sign up to set email alerts
|

High resolution melting curve analysis targeting the HBB gene mutational hot-spot offers a reliable screening approach for all common as well as most of the rare beta-globin gene mutations in Bangladesh

Abstract: BackgroundBangladesh lies in the global thalassemia belt, which has a defined mutational hot-spot in the beta-globin gene. The high carrier frequencies of beta-thalassemia trait and hemoglobin E-trait in Bangladesh necessitate a reliable DNA-based carrier screening approach that could supplement the use of hematological and electrophoretic indices to overcome the barriers of carrier screening. With this view in mind, the study aimed to establish a high resolution melting (HRM) curve-based rapid and reliable mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 36 publications
(30 reference statements)
7
60
0
Order By: Relevance
“…From the borderline suspected Group 2, a participant with 3.5% HbA2 generated a HRM curve pattern different from the wild type cluster (without mutation in HBB gene) and also did not match with any of the HRM curves previously established for all the reported mutations in Bangladesh [2]. Sanger sequencing identified and confirmed the suspected mutation as c.151A > G (ACT>GCT; Thr > Ala) in the HBB gene and upon BLAST with databases it was found to be a novel mutation, thereby confirming the carrier status of this participant ( Fig.…”
Section: Screening For Thalassemia Carriers Based On MCV Mch and Hemmentioning
confidence: 82%
See 4 more Smart Citations
“…From the borderline suspected Group 2, a participant with 3.5% HbA2 generated a HRM curve pattern different from the wild type cluster (without mutation in HBB gene) and also did not match with any of the HRM curves previously established for all the reported mutations in Bangladesh [2]. Sanger sequencing identified and confirmed the suspected mutation as c.151A > G (ACT>GCT; Thr > Ala) in the HBB gene and upon BLAST with databases it was found to be a novel mutation, thereby confirming the carrier status of this participant ( Fig.…”
Section: Screening For Thalassemia Carriers Based On MCV Mch and Hemmentioning
confidence: 82%
“…Since screening by hematological indices may result in misdetection of carriers due to factors like co-inheritance of αthalassemia, mutations in βand δ-globin genes, mutations in KLF1 gene and iron deficiency anemia [15,27,28], this study applied a comparatively cheaper and easy-to-perform DNA-based HRM curve analysis method to confirm and characterize mutations in the β-globin gene. This method supplements the conventional hematological and electrophoretic parameter based approaches for identification of the thalassemia carriers and patients [2]. For example, although the parameters MCV ≥ 80 fL and MCH ≥ 27 pg are usually considered as a negative indicator for HbE trait, our study using electrophoresis had identified two HbE carriers with MCV ≥ 80 fL and MCH ≥ 27 pg and a case having MCV > 80 fL and MCH < 27 pg as HbE carrier, indicating the shortcomings of hematological indices in screening of HbE carriers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations